Early Stage Cancer in Older Adults: Prostate—Avoiding Overtreatment and Undertreatment. Issue 4 (July 2017) - Narayan, Vikram; Jiang, Song; Warlick, Christopher A.
Abstract : Abstract: The diagnosis of prostate cancer in elderly men is likely to increase over the next several decades, owing to changing demographics and a rising population of men older than 65 years. Given the heterogeneity and well-documented challenges in screening, diagnosing, and managing indolent versus aggressive prostate cancer, the geriatric patient population is particularly vulnerable to prostate cancer treatment nuances. Clinicians must become familiar with geriatric assessment tools to better answer life-expectancy questions prior to counseling patients on treatment options. The preferences and values of patients and their families must always be considered when making screening and treatment decisions. Careful selection of patients following a holistic evaluation will not only minimize overtreatment and undertreatment of prostate cancer, but may also allow for the early identification of unique geriatric vulnerabilities and permit quicker interventions to improve the quality of life of these men during their elderly years.